ENSURING THE QUALITY OF TRAINING IN THE CONTEXT OF DIGITALISATION OF VOCATIONAL EDUCATION (Innovative professional education, 2024)
The work defines the requirements and tasks of ensuring quality education at the international, state and institutional levels; the importance of quality vocationaleducation for sustainable global development and recommendations for its achievement are highlighted; the essence of the concept of digitalization is revealed, the main principles of the development of the digital economy and society of the state are named, and proposals are made to ensure the quality of vocational training of specialists in the conditions of the implementation of digitalization in the educational sector.
Keywords: the quality of vocational education, the system of ensuring the quality of education; digitization; basic principles of digitization; ensuring the quality of education based on digital technologies